The Integration Of Qur’an And Linguistic Education Based On Ontology Of Qur’anic Concept In Quranic Arabic Corpus - Nur Ali; Mamluatul Hasanah; Agung Prasetyo (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
Users of Arabic and religious learning program applications are surprised by the phenomenon among students and teachers of Arabic and religious languages in which most of them have never practiced and used The Qur'anic Arabic Corpus (QAC) applications for academic activities. Meanwhile, the program has many benefits and conveniences for students, teachers, and researchers for conducting research and study activities in the field of language and religion and science integration. The number of open-source of IT-based information that can be used for Arabic language learning activities and studies of religious and scientific integration is increasing significantly. The purpose of this paper is to evaluate the understanding and use of The QAC program in teaching and learning Arabic and the integration of religious sciences in schools and colleges of Islamic religion. This study uses Krippendorf perspective qualitative design in the study of al-Qur'an integration and linguistic education. The research method used is the study of linguistic corpus with annotations, abstractions, and analysis through three stages of corpus exploration, experimentation, and knowledge discovery. Through data analysis, it is found that the Arabic and religious learning model using The QAC can improve language creativity and improvisation and improve the process of reciting, memorizing and vocabulary building, making it easier for students to study the integration of Qur'an, language, religion, and science. This paper recommends that Arabic and religious learning activities utilize IT-based learning program applications such as the QAC